Influence of Processing Techniques on Microstructure and Mechanical Properties of a Biodegradable Mg-3Zn-2Ca Alloy - Doležal, Pavel; Zapletal, Josef (MDPI, 2016)
New Mg-3Zn-2Ca magnesium alloy was prepared using different processing techniques: gravity casting as well as squeeze casting in liquid and semisolid states. Materials were further thermally treated; thermal treatment of the gravity cast alloy was additionally combined with the equal channel angular pressing (ECAP). Alloy processed by the squeeze casting in liquid as well as in semisolid state exhibit improved plasticity; the ECAP processing positively influenced both the tensile and compressive characteristics of the alloy. Applied heat treatment influenced the distribution and chemical composition of present intermetallic phases. Influence of particular processing techniques, heat treatment, and intermetallic phase distribution is thoroughly discussed in relation to mechanical behavior of presented alloys.

New Mg-3Zn-2Ca magnesium alloy was prepared using different processing techniques: gravity casting as well as squeeze casting in liquid and semisolid states. Materials were further thermally treated; thermal treatment of the gravity cast alloy was additionally combined with the equal channel angular pressing (ECAP). Alloy processed by the squeeze casting in liquid as well as in semisolid state exhibit improved plasticity; the ECAP processing positively influenced both the tensile and compressive characteristics of the alloy. Applied heat treatment influenced the distribution and chemical composition of present intermetallic phases. Influence of particular processing techniques, heat treatment, and intermetallic phase distribution is thoroughly discussed in relation to mechanical behavior of presented alloys.
Influence of Processing Techniques on Microstructure and Mechanical Properties of a Biodegradable Mg-3Zn-2Ca Alloy
Keywords: biodegradable magnesium alloy; Mg-Zn-Ca; squeeze casting; ECAP processing; microstructure; mechanical properties; biodegradable magnesium alloy; Mg-Zn-Ca; squeeze casting; ECAP processing; microstructure; mechanical properties